2020
DOI: 10.1016/j.jaad.2020.03.076
|View full text |Cite
|
Sign up to set email alerts
|

Survival in patients with multiple primary melanomas: Systematic review and meta-analysis

Abstract: Background:The literature surrounding survival of patients with multiple primary melanomas (MPM) yields variable and opposing findings, constrained by statistical challenges.Objectives: To critically examine the available literature regarding survival of patients with MPM compared with single primary melanomas (SPM) and detail statistical methods employed.Methods: Electronic searches of Pubmed, Embase, Web of Science and Scopus, with crosschecking of references, for the period January 1956 -June 2019 were carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Another study used delayed-entry methods and also found a worse survival for MPM patients [ 29 ]. Finally, it has also been suggested that including in situ melanomas in the survival studies does not influence the survival of MPM patients, and that it might dilute the opportunity to detect a real effect [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study used delayed-entry methods and also found a worse survival for MPM patients [ 29 ]. Finally, it has also been suggested that including in situ melanomas in the survival studies does not influence the survival of MPM patients, and that it might dilute the opportunity to detect a real effect [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, 82,476 new melanoma cases were reported in the USA, while about 7200 deaths due to melanoma were reported in 2019 [ 185 ]. Patients diagnosed with primary melanoma have a 5-fold higher risk of developing invasive melanoma with respect to the general population [ 186 ]. The early signs of melanoma include asymmetric lesions with irregular edges, a mottled color, ≥6 mm in diameter, and/or the rapid development of a new lesion, particularly in adults.…”
Section: Proapoptotic Effect Of the Wnt/β-catenin Pathway In Cancer Cellsmentioning
confidence: 99%